2016
DOI: 10.1111/ics.12340
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TRPV1 prevented skin irritancy induced by phenoxyethanol. A preliminary in vitro and in vivo study

Abstract: Different to capsaicin, phenoxyethanol did not downregulate the expression of TRPV1 in HaCaT cells, suggesting that different regulatory mechanisms may exist for capsaicin and phenoxyethanol. Our experiments demonstrated that phenoxyethanol induces skin misperception and uncomfortable skin sensations like itching and burning comparable to capsaicin via activating TRPV1. The stimulation was inhibited by blocking TRPV1 with ID1609. The present data strengthened hitherto studies that TRPV1 plays a critical role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Interestingly, TRPV1 immunoreactivity was lower in individuals with darker skin, suggesting that melanin might interfere with those factors that promote TRPV1 upregulation [67]. Perhaps related to these findings, the skin irritant phenoxyethanol was found to increase calcium influx into HaCaT cells in a manner inhibitable by TRPV1 antagonists [68]. Furthermore, it has been shown that retinoids evoke pain behavior in rodents by acting at TRPV1, presumably in neurons.…”
Section: Contributions Of Trp Channels To Skin Biology and Pathophmentioning
confidence: 99%
“…Interestingly, TRPV1 immunoreactivity was lower in individuals with darker skin, suggesting that melanin might interfere with those factors that promote TRPV1 upregulation [67]. Perhaps related to these findings, the skin irritant phenoxyethanol was found to increase calcium influx into HaCaT cells in a manner inhibitable by TRPV1 antagonists [68]. Furthermore, it has been shown that retinoids evoke pain behavior in rodents by acting at TRPV1, presumably in neurons.…”
Section: Contributions Of Trp Channels To Skin Biology and Pathophmentioning
confidence: 99%
“…Induction of hyperalgesic skin by the activation of the TRPV1 receptor with the chemical model substance capsaicin may seem to be quite an artificial system with poor practical relevance in the cosmetic field as no one would apply this compound to the skin without medical need. However, it has been shown that some chemical compounds relevant in cosmetics like phenoxyethanol or allergens can activate the TRPV1 receptor after a short lag time and a TRPV1 receptor blocker to prevent a burning and stinging perception induced by chemical compounds is therefore of an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that some chemical compounds relevant in cosmetics like phenoxyethanol or allergens can activate the TRPV1 receptor after a short lag time [6] and a TRPV1 receptor blocker to prevent a burning and stinging perception induced by chemical compounds is therefore of an advantage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations